Production of nickel-rich LiNi0.89Co0.08Al0.03O2 cathode material for high capacity NCA/graphite secondary battery fabrication - Yudha Cornelius Satria; Hutama Anjas Prasetya; Rahmawati Mintarsih; Arinawati Meidiana; Aliwarga Harry Kasuma (Kiwi); Widiyandari Hendri; Purwanto Agus (Open Engineering, 2022)
Li-ion secondary battery is highly recommended as a power source to highly advanced battery electric vehicles. Among various types, the lithium nickel cobalt aluminum oxide (NCA) battery is considered suitable for high energy and power application. In this study, the NCA cathode material LiNi0.89Co0.08Al0.03O2 was produced via the oxalate co-precipitation technique to reduce the overall production cost and process complexity. Oxalic acid and a small amount of sodium hydroxide were used as the precipitant and pH regulator, respectively. Homogenous and loose metal oxalate precipitate formation was confirmed by X-ray diffraction (XRD), scanning electron microscopy, and Fourier-transform infrared spectroscopy analysis. XRD patterns of the as-obtained micron-sized NCA showed a well-layered hexagonal structure. The electrochemical properties of the cathode in the full cell were thoroughly examined. The specific discharge capacity of the as-obtained NCA in NCA/LiPF6/graphite at a current rate of 20 mA/g was 142 mAh/g. The as-prepared NCA sample had capacity retention of 80% after being charged and discharged at 0.1 A/g for 101 cycles. Scaling up of NCA production process to 2 kg per batch was conducted and evaluation of NCA product quality was performed by material characterization. Based on the overall results and considering the overall process, such an approach is expected to be developed and improved for future large-scale production purposes.